2007
DOI: 10.1007/s12149-007-0010-6
|View full text |Cite
|
Sign up to set email alerts
|

2-[Fluorine-18]-fluoro-2-deoxy-d-glucose positron emission tomography/computed tomography versus whole-body diffusion-weighted MRI for detection of malignant lesions: initial experience

Abstract: DWIBS can be used for the detection of malignant tumors or benign tumors; however, it may be difficult to differentiate between benign and malignant lesions by ADC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 17 publications
2
66
0
3
Order By: Relevance
“…The role of DWIBS in the detection of extra-bone primary tumors has been demonstrated in a few experiences, with heterogeneous populations and low numbers of patients [15,16]. DWIBS imaging provides image with high contrast-to-noise ratio (CNR), leading to easy identification of small lesions during visual analysis and shortening reading time required to review the huge number of images provided by conventional WB-MRI.…”
Section: Discussionmentioning
confidence: 99%
“…The role of DWIBS in the detection of extra-bone primary tumors has been demonstrated in a few experiences, with heterogeneous populations and low numbers of patients [15,16]. DWIBS imaging provides image with high contrast-to-noise ratio (CNR), leading to easy identification of small lesions during visual analysis and shortening reading time required to review the huge number of images provided by conventional WB-MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion of water molecules in malignant tumors is usually restricted compared to that in normal tissue, resulting in a decreased apparent diffusion coefficient (ADC) value (Szafer et al, 1995;Takahara et al, 2004). Some recent studies comparing DWI with FDG-PET have shown that DWI at 1.5 T is comparable with FDG-PET for detecting malignant lesions (Komori et al, 2007;Nomori et al, 2008;Mori et al, 2008), and an meta-analysis has shown that DWI can be used to differentiate malignant from benign pulmonary lesions . It is uncertain whether DWI has advantages over FDG-PET for distinguishing malignant from benign pulmonary nodules and masses.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have recently reported that body diffusion-weighted magnetic resonance imaging (DWI) may be useful not only for detecting malignant tumors and their metastatic spreads with high conspicuity (7)(8)(9)(10)(11), but also for tumor characterization (12)(13)(14)(15)(16)(17)(18)(19). Usually malignant tumors, including metastatic lesions, show bright signal on DWIs, and the apparent diffusion coefficient (ADC) values of malignant tumors are lower than the corresponding value of benign tumors.…”
mentioning
confidence: 99%